Formal Variation and Language Change in Catalan Quantifiers: The Role of Pragmatics - Joan-Rafael Ramos (Universitat Autònoma de Barcelona, 2020)
This article studies the formal variation of the masculine singular forms of the quantifiers u/un ‘one’, algú/algun ‘someone, some’, ningú/ningun ‘no-one, anyone, not one, any, none’ and cada u/cada un ‘everyone, each one’ in contemporary Catalan. The standard uses of these forms are contrasted with dialectal uses, obtained from a thorough search in oral and written corpora. In addition, they are compared with the uses in the other Romance languages and with their historical evolution in Catalan. The whole set of data, and especially the dialectal information on the Valencian area, allow us to explain the various factors that have interacted in the variation and formal change of these quantifiers. Among these factors, the fundamental role of pragmatics stands out above the rest. It is shown that, given the polysemy and synonymy caused by vacillations between the variants of the quantifiers, strategies are sought to improve communicative effectiveness, so that the differentiation between form and function becomes firmly established in the majority of quantifiers. Other prominent factors are those of analogical and, above all, phonological nature, which, on the one hand, explain the syncretism of the form un, and, on the other, enable us to understand the reasons why in the Valencian area there is a process of substitution of genuine forms by borrowings from Spanish.